Calling things by their proper names: The truth about migration in a polarized world - Nurlan Rahimli (Transformation, Integration and Globalization Economic Research (TIGER), 2025)
Migration remains one of the most politicized and misunderstood phenomena in contemporary public discourse. This essay interrogates four persistent myths that continue to shape migration narratives: that global migration is historically unprecedented; that we are facing a large-scale refugee crisis; that poverty is the principal driver of migration; and that migrants constitute a burden on host societies. Drawing on robust empirical evidence - primarily from the work of Hein de Haas and leading international datasets - the author demonstrates that these claims do not withstand scrutiny. While the absolute number of international migrants has risen, their share of the global population has remained stable. Refugees comprise a small fraction of this total, and the notion of "crisis" often reflects political response more than demographic reality. Moreover, development tends to facilitate migration rather than suppress it, and migrants - contrary to popular belief - make net positive contributions to host economies over the long term. Rather than treating migration as an aberration or emergency, this paper argues for recognizing it as a structural and enduring dimension of global transformation. By replacing rhetoric with evidence and complexity with clarity, scholars and policymakers can foster more accurate, constructive, and equitable approaches to migration governance.
Keywords: 330; International migration; Refugees; Population development; World; Internationale Migration; Flüchtlinge; Bevölkerungsentwicklung; Welt